Association between Dental Prosthesis and Periodontal Disease among Patients Visiting a Tertiary Dental Care Centre in Eastern Nepal - Mansuri, M.; Shrestha, A. (Kathmandu University Medical Journal, 2017)
Background Dental caries and Periodontal diseases are the most prevalent oral health problems present globally. The distribution and severity of such oral health problems varies in different parts of the world and even in different regions of the same country. Nepal is one of the country with higher prevalence rate of these problems. These problems arise in association with multiple factors. Objective This study was carried out to describe the periodontal status and to analyse the association of periodontal disease with the wearing of fixed or removable partial dentures in a Nepalese population reporting to the College of Dental Surgery, B P Koirala Institute of Health Sciences, Dharan, Nepal. Method This study comprised of a sample of 200 adult individuals. All data were collected by performing clinical examinations in accordance with the World Health Organization Oral Health Surveys Basic Methods Criteria. It included the Community Periodontal Index and dental prosthesis examination. Result A descriptive analysis was performed and odds ratio (1.048) and 95% confidence interval (1.001; 1.096) was found out. The mean age of the population participated in the study was 41.82 ± 14.80 years. A total of 93 (46.5%) males and 107 (53.5%) females participated in the study. Among these subjects, 100% presented some periodontal problems. The statistical analysis indicated that the probability of periodontal disease with regards to wearing partial dentures was not significant as suggested by the odds ratio (1.048). Conclusion There is no association of the wearing of dental prosthesis (RPD and/or FPD) with the periodontal disease and suggests a need for populations based oral health education programs, plaque control programs to reduce the incidence of periodontal disease.